Volume and Cutting Optimization of Reinforcing Steel in Construction of a Satpol PP Building Project - Putri, Quini Athaya; Handayani, Fajar Sri; Setiono, Setiono (Indonesian Journal Publisher, 2024)
The world of construction is very dependent on technology, especially in the era of the industrial revolution which demands efficiency and competitiveness. The use of BIM (Building Information Modeling) technology supported by Autodesk Revit software enables more effective and efficient project planning and implementation. One application of BIM is in planning reinforcing steel requirements. To overcome material waste which often occurs due to less than optimal cutting of reinforcing steel, material management with a bar bending schedule and the use of BIM is an important solution. In the Satpol PP Building Construction Project in Bantul Regency by PT Quinad Bahana Indonesia, this new method with software was applied to correct cutting of reinforcing steel, reduce waste and increase construction efficiency. This research method includes data collection, 3D BIM modeling, comparing work volume using Autodesk Revit and conventional. After getting the reinforcing steel volume from the Autodesk Revit software, continue by entering the volume data into the BIM to obtain optimal reinforcing steel cutting patterns. The research results show that the use of Autodesk Revit software for column and beam work results in an overall difference of 11%. The volume resulting from Revit quantity take-off is less than manual analysis. Based on waste level calculations, the average value of waste level is 0.97%. This proves that the BIM is effective in reducing material waste on construction projects. Apart from reducing material waste, the BIM is also able to optimize reinforcing steel cuts.